METHODS OF TEACHING ENGLISH IN HIGHER EDUCATION IN UZBEKISTAN - Akramovna, Fazilova Nodira (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
Scientific content of the article is based opinions on improving the effectiveness of the educational process on the basis of modern teaching methods, interactive ideas in higher education. At the same time, one of the main goals is to provide students with the necessary conditions in the process of teaching and to show them on a scientific basis that they will become more knowledgeable, capable and mature professionals.